2020
DOI: 10.21474/ijar01/10354
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Demirjian and Cameriere Methods for Dental Age Estimation of Children Aged 5-13 Year in Delhi-NCR Region

Abstract: The purpose of this study was to comparative study of Demirjian and Cameriere methods for dental age estimation of children aged 5-13 year in DELHI-NCR region. Settings and Design: The design of this study was a retrospective study of panoramic radiographs. Randomly 40 selected digital panoramic radiographs of children, both males and females in mixed dentition period (5-13 years), taken as part of diagnostic procedure, showing all seven left permanent teeth. Results: In comparison with the present study done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The accurate estimation of an individual’s age is imperative for forensic analysis, medico-legal issues (i.e., criminal prosecution and management of immigration issues) and anthropology, with osteology-based and dental-based methodologies being most frequently utilized for this purpose [ 40 ]. Tooth development is often used to assess dental maturity and estimate dental age, which is not only important for the fields of forensic odontology and forensic dentistry but also for clinical diagnosis and treatment in paediatric dentistry [ 41 ]. Furthermore, dental radiographs are valuable for forensic and archaeology purposes to estimate age in the living and dead [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accurate estimation of an individual’s age is imperative for forensic analysis, medico-legal issues (i.e., criminal prosecution and management of immigration issues) and anthropology, with osteology-based and dental-based methodologies being most frequently utilized for this purpose [ 40 ]. Tooth development is often used to assess dental maturity and estimate dental age, which is not only important for the fields of forensic odontology and forensic dentistry but also for clinical diagnosis and treatment in paediatric dentistry [ 41 ]. Furthermore, dental radiographs are valuable for forensic and archaeology purposes to estimate age in the living and dead [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian yang sudah dilaksanakan ini, menggunakan Metode Cameriere pada 35 sampel foto radiografi panoramik anak-anak usia 5-15 tahun yang berada di Rumah Sakit Universitas Udayana (RS Unud) Bali dan menunjukkan hasil rata-rata usia pada sampel total yaitu Usia Gigi 0,09 tahun lebih tua dari Usia Kronologis, sesuai dengan penelitian yang dilakukan oleh Ranjan dkk pada tahun 2020 di Delhi menggunakan 40 sampel foto radiografi panoramik, yaitu rata-rata Usia Gigi pada sampel total lebih tua dari Usia Kronologis yaitu sebanyak 0,86 tahun. Jika dilihat pada data setiap pengelompokan usia, penelitian oleh Ranjan dkk pada tahun 2020 mendapatkan bahwa rata-rata Usia Gigi lebih tua dari Usia Kronologis baik pada kelompok usia 5-7 tahun, 8-10 tahun, dan 11-13 tahun, sedangkan pada penelitian ini kelompok usia 5-7 tahun Usia Gigi lebih tua dari Usia Kronologis dan kelompok usia lainnya menunjukkan bahwa Usia Gigi lebih muda dari Usia Kronologis (Tabel 2) 16 .…”
Section: Pembahasanunclassified
“…Moreover, some studies showed that both the methods are strongly correlated with chronological and dental ages and have potential relevance to estimating age in the Indian population, where authors such as Acharya have developed the Indian formula that has proved effective in the evaluation of DA. [ 11 12 ]…”
Section: Introductionmentioning
confidence: 99%